Adjustment with a human face : country case studies. vol. 2 - Cornia, G. A., ed. (Oxford University P. OxfordGB, 1988)
Contains studies of 10 countries from Asia, Africa, Latin America and the Caribbean illustrating how the adverse economic developments and consequent stabilization and adjustment policies experienced by the majority of developing countries have affected vulnerable groups especially children. For each country describes the initial conditions, analyses the nature of economic shocks and changes in policies and critically assesses the country's performance in terms of economic growth and key child welfare indicators.